2007
DOI: 10.1021/bc700147j
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer between CdSe/ZnS Core/Shell Quantum Dots and Fluorescent Proteins

Abstract: Fluorescent proteins from the green fluorescent protein (GFP) family interact strongly with CdSe/ZnS quantum dots. Photoluminescence of GFP5 is suppressed by red-emitting CdSe/ZnS quantum dots with high efficiency in a pH-dependent manner. The elevated degree of quenching, around 90%, makes it difficult to analyze the remaining signal, and it is not clear yet whether FRET is the reason behind the quenching. When the donor is a green-emitting CdSe/ZnS quantum dot and the acceptor is the HcRed1 protein, it is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 30 publications
0
34
0
3
Order By: Relevance
“…While good spectral overlap is of paramount importance to high transfer efficiency, the donor and acceptor photoluminescence signals must also be well resolved to extract accurate experimental information for the system under investigation [15,26]. It has also been possible to assemble hybrid nanoparticle-protein/DNA comprising QDs simultaneously coupled to dye labelled proteins, oligonuceotides and dyes [27,28]. This study also reported the occurrence of FRET beyond 100 Å. Medintz et al [29,30] have demonstrated FRET using CdSe-ZnS (core-shell) QD donors self assembled with three distinct fluorescent protein acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…While good spectral overlap is of paramount importance to high transfer efficiency, the donor and acceptor photoluminescence signals must also be well resolved to extract accurate experimental information for the system under investigation [15,26]. It has also been possible to assemble hybrid nanoparticle-protein/DNA comprising QDs simultaneously coupled to dye labelled proteins, oligonuceotides and dyes [27,28]. This study also reported the occurrence of FRET beyond 100 Å. Medintz et al [29,30] have demonstrated FRET using CdSe-ZnS (core-shell) QD donors self assembled with three distinct fluorescent protein acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, numerous proteins in which the opto-electronic functionality is already encoded into the protein structure. Examples are fluorescent proteins [6,11,12] or the light-harvesting complex of the photosynthetic apparatus in green plants (LHCIIb) consisting of a scaffold protein that binds numerous different chromophores at an exceptionally high density [13]. Its major function is to greatly enhance the efficiency of photosynthesis by collecting light energy, which then is conducted to the photosynthetic reaction centers where the excitation energy is converted to chemical potential.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is very simple and efficient when compared to conventional LbL methods based on electrostatic interaction which is complicated by a serious PL quenching and the solution stability (i.e., the small ligands with thiol and carboxylic acid groups or the control of solution pH). [31][32][33] Figure 5b shows the change in the UV-Vis spectra occurred from (PAH/spiropyran-BCM) 10 multilayers before and after UV irradiation. This means that upon irradiation with 375 nm UV light for 6 min, the UV-Vis absorption spectra of (PAH/spiropyran-BCM) 10 films containing spiropyran showed a decrease in the absorption peak at 367 nm (spiropyran form) and the growth of a new absorption peak at 552 nm (merocyanine form).…”
Section: Optical Filmsmentioning
confidence: 99%